2016
DOI: 10.1158/0008-5472.can-16-1521
|View full text |Cite
|
Sign up to set email alerts
|

Eph Receptor Tyrosine Kinases in Tumor Immunity

Abstract: The family of Eph receptor tyrosine kinases and their ephrin ligands regulate a diverse array of physiological processes, such as axonal guidance, bone remodeling, and immune cell development and trafficking. Eph/ephrin interactions have also been implicated in various pathological processes, including inflammation, cancer, and tumor angiogenesis. Because Eph receptors play prominent roles in both the immune system and cancer, they likely impact the tumor immune microenvironment, an area in which Eph receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…Identification of metabolic targets that are selectively utilized in tumor cells may greatly improve antitumor immunity by avoiding detrimental effects on the immune cells. For example, the receptor tyrosine kinase EphA2 promotes glutamine metabolism in HER2-positive and triple-negative breast cancer cells (67,68), but it is not expressed in the T cells (69). Targeting EphA2 may selectively inhibit glutaminolysis in tumor cells while simultaneously avoiding similar effects on T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of metabolic targets that are selectively utilized in tumor cells may greatly improve antitumor immunity by avoiding detrimental effects on the immune cells. For example, the receptor tyrosine kinase EphA2 promotes glutamine metabolism in HER2-positive and triple-negative breast cancer cells (67,68), but it is not expressed in the T cells (69). Targeting EphA2 may selectively inhibit glutaminolysis in tumor cells while simultaneously avoiding similar effects on T cells.…”
Section: Discussionmentioning
confidence: 99%
“…10F,G). EPHA2 has been previously identified as a highly expressed surface protein in OS cells and tissue [41][42][43] . We found that LGALS1, a potent inducer of T-cell apoptosis 44,45 , was LGALS1 upregulation has been reported in human OS tissue samples 46 and is associated with metastatic and aggressive cancer cell phenotypes [47][48][49] .…”
Section: Figure 5 Prm-based Confirmation Of Hypoxia-induced Expressimentioning
confidence: 99%
“…2 These receptors are wellestablished mediators in cell-cell interactions and motility and are expressed in human cancers, including melanoma, prostate, breast, colon, lung and esophageal carcinomas. 3 Among these receptors, EphA2 plays important roles in oncogenesis, metastasis and treatment resistance. 4 In ES, we demonstrated the involvement of EphA2 in tumor progression by promoting angiogenesis in a ligand-dependent manner.…”
Section: Introductionmentioning
confidence: 99%